Two new Acronicta Ochsenheimer, 1816 from China and Russia (Lepidoptera, Noctuidae, Acronictinae) - Kononenko, Vladimir; Han, Hui-Lin (Zootaxa, 2008)
Based on museum and private collections, two new species of the subfamily Acronictinae are described from China and Russia, Transbaikalia and Primorye Territory: Acronicta (Triaena) psichinensis sp. n. and Acronicta (Viminia) dahurica sp. n. The adults and male and female genitalia of the new species are illustrated and compared to related species. Distribution maps for the new species are presented.